Research on the Creative Transformation and Innovative Development of the San Li Family Ethos — A Practical Exploration Based on Character Building for Primary School Students - Chen, Pengyu; Chen, Tang (Journal of Research in Vocational Education, 2025)
This study focuses on the creative transformation and innovative development of the Three Lis family ethos—referring to Li Diaoyuan, Li Dingyuan, and Li Jiyuan, prominent scholars of Mianzhou in the Qing Dynasty—and explores its practical application in character building for primary school students. Rooted in the rich cultural heritage of the Three Lis, which emphasizes moral integrity, scholarly pursuit, and family harmony, this research addresses the challenge of adapting traditional family values to contemporary educational contexts. By integrating theoretical analysis with hands-on practice, the study designs a series of age-appropriate educational activities, including story-telling sessions, role-playing, and project-based learning, to translate the essence of the Three Lis ethos into tangible moral lessons. Empirical data collected from primary school students over six months indicate that such tailored interventions not only enhance students’ understanding of traditional virtues but also significantly improve their self-discipline, empathy, and sense of social responsibility. The findings highlight the feasibility of bridging historical family culture with modern character education, providing a replicable model for the inheritance of intangible cultural heritage in youth development. This exploration underscores the importance of contextualizing traditional ethos to foster holistic personality growth in the new era, contributing to both cultural preservation and educational innovation.